2005
DOI: 10.1016/j.ijsolstr.2005.03.016
|View full text |Cite
|
Sign up to set email alerts
|

An analytical and numerical approach for calculating effective material coefficients of piezoelectric fiber composites

Abstract: The present work deals with the modeling of 1-3 periodic composites made of piezoceramic (PZT) fibers embedded in a soft non-piezoelectric matrix (polymer). We especially focus on predicting the effective coefficients of periodic transversely isotropic piezoelectric fiber composites using representative volume element method (unit cell method). In this paper the focus is on square arrangements of cylindrical fibers in the composite. Two ways for calculating the effective coefficients are presented, an analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(167 citation statements)
references
References 30 publications
10
152
1
4
Order By: Relevance
“…(2)) have been calculated for one specific fiber volume fraction, that is, 55.5%. The method is applied and the results are compared with analytical and numerical results available in the technical literature by Berger et al (2005) and Moreno et al (2009), respectively. The results are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2)) have been calculated for one specific fiber volume fraction, that is, 55.5%. The method is applied and the results are compared with analytical and numerical results available in the technical literature by Berger et al (2005) and Moreno et al (2009), respectively. The results are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The material properties related to the epoxy resin (composite matrix) and piezoelectric fiber (PZT-5A) were taken from Berger et al (2005) and are shown in Table 1, according to orthotropic directions (coordinate system 1-2-3). For theses analyses presented, a fiber volume fraction of 55.5% for circular section, and also, for square section fiber was adopted and the fiber is oriented in direction 3.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some analytical methods from the composite materials literature, such as the Asymptotic Homogenization Method (AHM) (Benjeddou and Al-Ajmi, 2009;Otero et al, 2005) and the Uniform Field Method (UFM) (Bent and Hagood, 1997) can be applied to obtain the effective properties of the composite transducer active core from the properties of its components. Alternatively, one may use techniques based on finite element modelling of the composite transducer active core to identify its effective properties (Berger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%